Perspectives for the textiles and clothing industry in Greece: Past experience, outlook and policy implications - Dimitrios Dadakas; Stelios D. Katranidis (SPOUDAI - Journal of Economics and Business, 2011)
The liberalization of trade in Textiles and Clothing (T&C) had substantial adverse effects on the Greek T&C industry. The elimination of export quotas affected production levels, exports, prices and employment in the sector. Using past research results we explore how the MultiFiber Agreement (MFA) and the, subsequent, Agreement on Textiles and Clothing (ATC) regime affected producers' welfare in Greece. Given the recent developments, after the 2005 termination of the ATC, we explore the applicability of a policy model. Innovations adopted in the production process, new cost-efficient technologies and workers' training are the keystone factors in establishing a competitive industry for the future.
Keywords: D20; D60; F10; L67; 330; T&C; MFA; ATC; Applied Welfare Analysis